An examination of the cross-sectional relationship of beta and return in international stock returns: evidence from emerging and developed markets - Spierts, Joshua Patrick (2018)
This paper will follow Pettengill et al.’s (1995) approach to examine the unconditional and conditional relationship between beta and returns from January 1995 to May 2017 in a well globally diversified sample of 22 emerging markets and 23 developed markets. Additionally, Pettengill et al.’s (1995) methodology is adjusted to take into account 1-year time-varying beta values to supplement and check the robustness of the initial results. The empirical results for the full sample as well as both sub-samples indicate that there is no significant unconditional relationship between beta and returns, however, when differentiating between up- and down-markets a significant conditional relationship is found. This paper adds to the existing literature by examining and comparing a large sample of both developed and emerging markets, as well as, confirming the results according to Pettengill et al.’s methodology with timevarying betas.